Energy storage system configuration in power distribution network considering partitioned resource coordination - Shi, Jing; Zhou, Jiachen; Zhang, Zitong; Liu, Qi; Cheng, Qi; Cheng, Siwei; Ren, Li; Yang, Zili (Electric power systems research, 2025)
•Considering the connectivity of the power distribution network's topological structure and the electrical coupling between nodes, a similarity matrix based on the coupling and active power matching between nodes is established. And a graph based spectral clustering algorithm is proposed to partition the network's topology.•Based on the partitioning results of the power distribution network, a two-layer optimization configuration for ESS is proposed. The method considers the interaction of ESS and distribution network operation in each cluster, with the location and capacity of ESS optimized by outer layer and the operation of ESS optimized by inner layer interactively, which can improve the effectiveness of ESS configuration.•As the decision variables of the outer layer of optimization, the location and configuration parameters of ESS have spatial discreteness and numerical continuity, respectively. A tabu search algorithm which imbedded power flow calculation is proposed, and constrains of ESS’s location are set to enable a more refined search within clusters in power distribution network. The new distribution network introduces a large number of distributed resources, which brings some challenges to its safe and economic operation. Furthermore, the extensive application of advanced measurement technology leads to the quantification of the operating data. The distributed control with regional autonomy function can reduce the requirement of communication and realize the optimal control of the system, which has a wide application prospect. In addition, ESS is an important means to improve the flexibility of new power systems, so rational allocation of ESS in the distribution network can effectively improve the optimization control effect. In this paper, an ESS optimization configuration for power distribution network considering resource partition coordination is proposed. Firstly, the node similarity matrix is established based on the coupling and active power matching between nodes, and the spectral clustering algorithm is employed to divide the power distribution network into node clusters. Secondly, considering the interaction of ESS and distribution network operation in each zone, a dual-layer optimal configuration model is established, with the location and capacity of ESS optimized by outer layer and the operation of ESS optimized by inner layer interactively. Lastly, a case study of IEEE-33 power distribution network with wind and photovoltaic power generation is carried out to verify the effectiveness of proposed method.